Flexographic printing of ultra-thin semiconductor polymer layers - Davide Deganello (Translational Materials Research, 2016)
Methods of fabricating and controlling organic light emitting diode (OLED) or photovoltaic layers effectively are paramount for achieving a functional and durable device. The deposited film needs to be uniform and homogeneous to avoid non-uniform luminescence in the OLED. Although methods of depositing the ultra-thin sub 100 nm layers within OLED are effective, they are relatively slow and expensive. This paper therefore demonstrates flexography as an alternative method for depositing the semiconductor layer for OLED onto glass substrate. In this case a proprietary semiconducting polyflourine dispersed in xylene was used. This material functions as the hole injecting layer. The low polymer concentration and requirement for aromatic solvent presented challenges for the process; conventional photopolymer printing plates degraded rapidly on contact with xylene and rubber printing plates were found to be sufficiently resilient. Through optimisation of printing parameters and surface modification of both the printing plate and substrate with UV/ozone exposure, a consistent sub-100 nm film was achieved. Flexographic printing will enable a substantial reduction in layer fabrication time, as well as allowing roll to roll mass production at lower cost. The research indicated within this paper will aid the progression of flexography as a viable cost effective method for OLED or display technology application through continuous printing of ultra-thin layers.